Beginning Xcode: Swift Edition - Knott, Matthew (Apress : Imprint: Apress, 2014)
Beginning Xcode, Swift Edition will not only get you up and running with Apple's latest version of Xcode, but it also shows you how to use Swift in Xcode and includes a variety of projects to build. If you already have some programming experience with iOS SDK and Objective-C, but want a more in-depth tutorial on Xcode, especially Xcode with Apple's new programming language, Swift, then Beginning Xcode, Swift Edition is for you. The book focuses on the new technologies, tools and features that Apple has bundled into the new Xcode 6, to complement the latest iOS 8 SDK. By the end of this book, you'll have all of the skills and a variety of examples to draft from to get your Swift app from idea to App Store with all the power of Xcode.